2005
DOI: 10.1128/jvi.79.6.3382-3390.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sites in Adenovirus Hexon for Foreign Peptide Incorporation

Abstract: Adenovirus type 5 (Ad5) is one of the most promising vectors for gene therapy applications. Genetic engineering of Ad5 capsid proteins has been employed to redirect vector tropism, to enhance infectivity, or to circumvent preexisting host immunity. As the most abundant capsid protein, hexon modification is particularly attractive. However, genetic modification of hexon often results in failure of rescuing viable viruses. Since hypervariable regions (HVRs) are nonconserved among hexons of different serotypes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
103
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 51 publications
(58 reference statements)
1
103
1
Order By: Relevance
“…The hypervariable region 5 (HVR5) surface loop of hexon is another attractive site for possible ligand incorporation because of its sheer abundance (720 copies) in the Ad virion. With the exception of the 71 amino acid BAP from P. shermanii , this site has only been shown to accommodate small insertions like RGD, His 6 , and other epitopes [Crompton et al, 1994, Vigne et al, 1999, Wu et al, 2005.…”
Section: Genetic Modification Of the Capsid: Introducing New Tropismmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypervariable region 5 (HVR5) surface loop of hexon is another attractive site for possible ligand incorporation because of its sheer abundance (720 copies) in the Ad virion. With the exception of the 71 amino acid BAP from P. shermanii , this site has only been shown to accommodate small insertions like RGD, His 6 , and other epitopes [Crompton et al, 1994, Vigne et al, 1999, Wu et al, 2005.…”
Section: Genetic Modification Of the Capsid: Introducing New Tropismmentioning
confidence: 99%
“…Detailed structural data on the major capsid proteins [Rux & Burnett, 2000,Xia et al, 1994 have greatly facilitated the genetic incorporation of foreign peptides and proteins into exposed regions of the Ad capsid. Initial work demonstrated that short peptides and epitopes could successfully be grafted into the surface exposed HI loop ] and C-terminus [Wickham et al, 1996] of the fiber knob domain, the RGD-containing loop of penton base [Wickham et al, 1997], the hypervariable region 5 (HVR5) loop of the hexon [Crompton et al, 1994,Wu et al, 2005, and the C-terminus of protein IX .…”
Section: Genetic Modification Of the Capsid: Introducing New Tropismmentioning
confidence: 99%
“…Subsequent work has verified that a hexahistidine tag can be inserted into HVR2, HVR3, HVR5, HVR6, and HVR7 without compromising virus viability (66). Initial studies attempting to take advantage of the malleability of HVRs were primarily focused on inserting short sequences to attain vector retargeting (63).…”
mentioning
confidence: 99%
“…Further experiments revealed the possibility of expanding the vector tropism by inserting a heparinbinding domain (Wickham et al, 1996), or an Arg-Gly-Asp (RGD)-containing peptide into the fiber knob (Dmitriev et al, 1998). Although different studies indicated the feasibility to target vectors to specific cell types, genetic modification often resulted in failure to rescue viable viruses, or in an impaired virus packing, peptide exposure, and vector transduction (Leissner et al, 2001;Wu et al, 2005). Because the insertion of a pre-selected peptide into a fiber knob often fails to generate an adenovirus vector, use of random peptide libraries displayed directly on the AdV capsid allows isolation of viable vectors with high affinity for specific tissues or cells (Miura et al, 2007).…”
Section: Genetic Modification Of the Adv Capsidmentioning
confidence: 99%